Alameda County State College [Bulletin] Summer Session 1963 - Alameda County State College:::::: (California State Printing Office; Alameda County State College, 1963)
A catalog of courses offered by Alameda County State College for the summer session of 1963. Includes academic calendar, names of faculty and administrators, and descriptions of courses and workshops offered.